Study on strength, durability and transport properties of cementitious systems admixed with sodium nitrite based corrosion inhibitor - Ahamed, S. Shafeer; Mohammed, M.S. Haji Sheik; Sridhar, R.; Roopa, V. (Journal of Structural Engineering, 2024)
This experimental investigation analyses the strength, durability and transport properties of cementitious systemsadmixed with sodium nitrite based corrosion inhibitor. The influence of inhibitor incorporation on workability,strength (compression, flexure and splitting tensile strength), durability (resistance to rapid chloride penetration(RCPT), accelerated corrosion (ACT)) and transport mechanism (water absorption and sorptivity) of cement concreteand cement mortar were assessed. In addition, morphology studies were also conducted through SEM. The concreteof grade M25 and cement mortar of mix ratio 1:3 were adopted. The workability of cement concrete and mortarwas maintained similar, irrespective of inhibitor addition at 1%, 2% and 5% by weight of binder (bwob). It is foundthat the addition of inhibitor does not affect the setting time guidelines proposed by Indian standards. There is areduction in water-cement ratio due to incorporation of inhibitor in concrete / mortar at higher dosages (2% and5% bwob). Appreciable to significant increase in compression, flexural and splitting tensile strength for InhibitorAdmixed Concrete (IAC) as compared to control concrete, irrespective of dosage addition. RCPT test results indicatethe performance grade of control and inhibitor admixed concrete as IAC5%> IAC2%> IAC1%> CC. In ACT, theperformance factor was 1.3 - 1.9 for inhibitor admixed mortar when compared with control mortar. Inhibitor AdmixedMortar (IAM) also exhibits appreciable reduction in pore formation and water absorption. The SEM image analysisconducted on 2% IAM, revealed an improved microstructure and cement hydrate formation. The improved strengthand durability performance of inhibitor admixed concrete / mortar may be due to (i) enhanced passivation layer onsteel surface, (ii) action of chloride repulsion mechanism (iii) reduction in water-cement ratio for similar workabilityand (iv) improved microstructure exhibited by the ingredients of corrosion inhibitor.